Project Based Learning as an Instructional Approach in Interprofessional Education: Students’ Perspectives and Learning Experiences - Fais Wahidatul Arifatin (Jompa Research and Development, 2026)
Interprofessional Education is essential in preparing students to collaborate effectively across professional disciplines in addressing complex real-world problems. One instructional approach that has gained increasing attention in higher education is Project-Based Learning, as it emphasizes active learning, collaboration, and authentic tasks. This study aims to explore students’ perspectives and learning experiences regarding the implementation of Project-Based Learning as an instructional approach in an Interprofessional Education course. Using a qualitative research design, data were collected from undergraduate students enrolled in an IPE course through reflective journals, focus group discussions, and semi-structured interviews. The data were analyzed thematically to identify recurring patterns related to students’ perceptions and experiences. The findings reveal that Project-Based Learning facilitates meaningful interprofessional collaboration, enhances communication skills, and promotes critical thinking and problem-solving abilities. Students also reported increased awareness of professional roles and responsibilities, as well as improved teamwork and mutual respect among different disciplines. However, challenges such as coordination difficulties, unequal participation, and time management issues were also identified. Overall, the study concludes that Project-Based Learning is an effective instructional approach in Interprofessional Education, providing authentic learning experiences that support the development of interprofessional competencies. The findings offer pedagogical implications for educators in designing and implementing IPE courses that foster collaborative and experiential learning environments.